2014 IEEE/ACM International Conference on Advances in Social Networks Analysis and Mining (ASONAM 2014) 2014
DOI: 10.1109/asonam.2014.6921589
|View full text |Cite
|
Sign up to set email alerts
|

Time-aware reciprocity prediction in trust network

Abstract: Study of reciprocity helps to find influential factors for users building relationships, which greatly facilitates the social behavior understanding in trust networks. In the previous literature, the dynamics of both network structure and user generated content are rarely considered. Our investigation of the available timing information from a real-world network demonstrates that time delay has significant impact on reciprocity formation. In particular, we find structural factors possess greater effect on shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Authors of (Cheng et al, 2011) compared structural differences of reciprocal links and parasocial links and they also studied a Twitter dataset and corresponding node features to predict reciprocal links. In another work (Feng et al, 2014), the authors reported that the majority of reciprocating links are created within a very short time after the creation of corresponding parasocial links. B. Dumba et al (Dumba et al, 2016) studied the structural properties of a reciprocal network and discussed user behavior patterns.…”
Section: Related Workmentioning
confidence: 99%
“…Authors of (Cheng et al, 2011) compared structural differences of reciprocal links and parasocial links and they also studied a Twitter dataset and corresponding node features to predict reciprocal links. In another work (Feng et al, 2014), the authors reported that the majority of reciprocating links are created within a very short time after the creation of corresponding parasocial links. B. Dumba et al (Dumba et al, 2016) studied the structural properties of a reciprocal network and discussed user behavior patterns.…”
Section: Related Workmentioning
confidence: 99%
“…Instead, in [13], the reciprocity prediction problem is modeled as an outlier detection problem. Feng et al [10] show that the time delay of the reciprocity relations also has a significant impact on the reciprocity formation. Therefore, they propose a time-aware reciprocity relation prediction model by employing the reciprocity time delay.…”
Section: Reciprocity Analysis and Predictionmentioning
confidence: 99%
“…It has implications in applications that range from friend recommendation [40], bursty prediction [30], information propagation [34] to viral marketing [22]. Recent years have witnessed increasing attempts to study user reciprocal behaviors [8,10,13,32]. Nonetheless, these methods predominantly dedicated to predicting if a parasocial link will be reciprocated back in the future given a snapshot of current network topology.…”
Section: Introductionmentioning
confidence: 99%